A systematic assessment of stress insomnia as the high-risk factor for cervical cancer and interplay of cervicovaginal microbiome - Rai, Ravina; Nahar, Manisha; Jat, Deepali; Gupta, Neelima; Mishra, Siddhartha Kumar (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical cancer is a dreaded form of cancer in women, the fourth most common cancer, with around 0.3 million females suffering from this disease worldwide. Over the past several decades, global researches have focused on the mitigation of cervical lesions and cancers and have explored the impact of physiological and psychological stress and insomnia on cervical pathogenesis. Furthermore, disruption of the cervicovaginal microbiome profiles is identified as an added high-risk factor for the occurrence of cervical cancer. The physiological regulation of stress has an underlying mechanism controlled via hypothalamic pituitary adrenal (HPA) and sympatho-adrenal medullary (SAM) axes. Disruptions in these axes have been identified as the factors responsible for maintaining the homeostasis balance. Recent studies on microbiomes have offered novel ways to combat cervical cancer and cervix infection by exploring the interplay of the cervicovaginal microbiome. Moreover, the integration of various immune cells and microbiome diversity is known to act as an effective strategy to decipher the cervix biological activity. Cytokine profiling and the related immune competence, and physiological stress and insomnia impart to the regulatory networks underlying the mechanism which may be helpful in designing mitigation strategies. This review addressed the current progress in the research on cervical cancer, HPV infection, immune cell interaction, and physiological stress and insomnia with the cervicovaginal microbiome to decipher the disease occurrence and therapeutic management.